Effect of pressurization frequency and duration on the consolidation of a dredged soil using air booster vacuum preloading combined with prefabricated horizontal drains. Issue 1 (February 2023) - Wang, Jun; Fu, Hongtao; Zhang, Weikai; Ni, Junfeng; Li, Xiaobing; Cai, Ying
Abstract: The prefabricated horizontal drain (PHD) clogging problem often results in poor drainage and consolidation effects. To solve this problem, this paper adopts air booster vacuum preloading combined with PHDs to treat dredged soil. Laboratory model tests and microscopic tests are used to investigate the improvement effect of this method on dredged soil consolidation at different pressurization frequency and duration. The test results indicate that pressurization can effectively relieve clogging and improve the consolidation efficiency. The frequent pressurization is conducive to the consolidation at the same air-boost ratio, and the longer pressurization duration has an obvious promoting effect in the later stage of consolidation at the same pressurization frequency. Furthermore, pressurization can significantly alleviate the PHDs clogging problem has also been demonstrated from the micro perspective. These findings could provide an important reference for the treatment of dredged soil by air booster vacuum preloading combined with PHDs. Highlights: Results show that it is superior to the conventional vacuum preloading method. Microcosmic experiments show that this method can effectively alleviate the clogging problem. The pressurization behavior at high frequency is better than that at low frequency at the same air-boost ratio. The improvement effect of the optimal pressurization duration on soil varies with time at the same frequency.